Foreign Investment inflows and Sectoral growth pattern in India- An Empirical study - Bhattacharya, Mousumi (Serbian Journal of Management, 2013)
The paper aims to study the causal relationship between foreign investment inflows and sectoral growth pattern of the three main sectors namely primary, secondary and tertiary sector of the Indian economy during the post liberalization period (1996-97:Q1 to 2009-10:Q2). Using Granger causality test conducted in a multivariate VAR framework, bidirectional causality is observed between foreign investment inflows and secondary sector growth. It is seen that tertiary sector growth causes foreign investment inflows. Regression analysis is also done with the same dataset and it reveals that both secondary sector growth and tertiary sector growth have led to foreign investment inflows to the economy after 1990 reforms.